ARDL analysis of remittance and per capita growth nexus in oil dependent economy: The Nigeria's experience - Mathew Rotimi; Mishelle Doorasamy; Udi Joshua; Grace Rotimi; Confort Rotimi; Gabriel Samuel; Gbenga Adeyemi; Ayodele Alemayo; Alfred Kimea (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2023)
Purpose: Remittance is essential to economic wellbeing, Realising this fact, this study examined, within the optimist theoretical framework, whether international remittances significantly impact per capita economic growth in Nigeria. Design/methodology/approach: Employing annual time series data spanning 1980-2020, the study adopted the Pesaran, Shin, and Smith ARDL bounds estimating model to examine the type of relationships between remittances and Nigeria's per capita growth. Finding: The study reveals a statistically significant positive nexus in the long-run and short-run among the variables, Specifically, it found that higher remittances inflow enhances per capita growth both in long-run and short-run in Nigeria, Furthermore, the study found that remittances are sources of external financing and eventually, it is a means to economic growth and also may help to fill fiscal deficit gap. Research limitations/implications: This study recommends that government should, through sound policy option, encourage remittances influx, This could be realised by creating viable relationship among international communities that largely account for remittance inflow into Nigeria, It further suggests a prudent and optimal management of remittances inflow through the appropriate monetary authority, This may include formulating policy that will ease remittance inflow and remove unnecessary barriers to inflow of remittances. Originality/value: The study contributes to literature by examining whether international remittances within the optimist theoretical framework significantly impact per capita economic growth (PCEG) in Nigeria.
Keywords: O47; F43; F24; C22; 330; Remittances; Per Capita; ARDL; Growth; Oil Dependent; Nigeria